Exchange rate pass-through to consumer prices: Theory and recent evidence - Laurence Savoie-Chabot; Mikael Khan (Bank of Canada, 2015)
In an open economy such as Canada's, exchange rate movements can have a material impact on consumer prices. This is particularly important in the current context, with the significant depreciation of the Canadian dollar vis-a-vis the U.S. dollar since late 2012. This paper provides a broad overview of the various mechanisms by which exchange rate movements pass through to consumer prices and discusses the implications of exchange rate pass-through (ERPT) for the conduct of monetary policy. It then describes some of the tools used at the Bank of Canada to help quantify ERPT. We conclude by taking a closer look at the current situation in Canada, presenting a range of evidence that suggests ERPT has played an important role in recent inflation dynamics. – – Dans une économie ouverte comme le Canada, les mouvements du taux de change peuvent avoir une incidence considérable sur les prix à la consommation. Ce constat revêt une importance particulière dans le contexte actuel où le dollar canadien s'est fortement déprécié depuis la fin de 2012 par rapport à la devise américaine. Dans cette étude, les auteurs brossent un portrait des divers mécanismes par lesquels les variations du taux de change se répercutent sur les prix à la consommation et analysent les conséquences de ce phénomène de transmission pour la conduite de la politique monétaire. Ils décrivent ensuite certains des outils qu'utilise la Banque du Canada pour mesurer le degré de transmission des mouvements de change. En conclusion, ils examinent de plus près la situation actuelle au Canada et présentent un éventail de faits qui donnent à penser que la transmission des variations du taux de change a grandement influé sur la dynamique récente de l'inflation.
Keywords: E31; E52; F31; 330; Exchange rates; Inflation and prices; Taux de change; Inflation et prix